As an analgesic ketamine versus fentanyl for total intravenous anesthesia - Ezici, Musa; Bestas, Azize; Erhan, Omer Lutfi (My University, 2013)
[Abstract Not Available]
Keywords: fentanyl; ketamine; midazolam; propofol; abdominal surgery; adult; analgesia; anesthesia induction; anesthesia level; anesthetic recovery; disease severity; drug effect; drug safety; elective surgery; heart rate variability; hemodynamic monitoring; human; inguinal hernia; intravenous anesthesia; letter; major clinical study; male; mean arterial pressure; postoperative care; postoperative pain; priority journal; pulse oximetry; unspecified side effect